Kepedulian Tokoh Terhadap Lingkungan Alam dalam Novel Kokokan Mencari Arumbawangi karya Chynta Hariadi - Muhamad Yuda Firdaus; Ferina Meliasanti; Imam Muhtarom (Peneliti.net, 2022)
This research is motivated by the amount of natural damage caused by the lack of awareness of the attitude of caring for the environment. The purpose of this research is to describe the character's caring attitude towards the natural environment in the novel Kokokan Seeking Arumbawangi by Chynta Hariadi. This research is a qualitative research with analytical descriptive method. The subject of this research is the novel Kokokan Searching for Arumbawangi by Cyntha Hariadi. While the object of this research is the character's concern for the natural environment in Cyntha Hariadi's novel Kokokan Seeking Arumbawangi . Data collection techniques in this study are library techniques, reading techniques, and note-taking techniques. Data analysis techniques in this study are data reduction, data presentation, and drawing conclusions. The results of the analysis of the character's concern for the natural environment include: respect for nature; attitude of moral responsibility towards nature; solidarity attitude towards nature; an attitude of compassion and concern for nature; and an attitude of not interfering with natural life.